Development of Differentiated Learning-Based Interactive E-Modules to Facilitate Student Learning Styles in Indonesian History Courses Islamic Period - Arfan Diansyah; Yushar Yushar; Syahrul Nizar Saragih; Abd. Haris Nasution (Universitas Negeri Malang, 2024)
This study aims to develop e-modules tailored to students' learning styles to improve learning effectiveness. A mixed-methods approach was employed, using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. A needs analysis was conducted through student interviews to identify their learning preferences. In the design phase, a prototype e-module was created using the Flip Book Maker application to accommodate various learning styles. During development, the e-module was validated by subject matter and media experts and tested with both small and large student groups. The effectiveness of the e-modules was assessed through learning outcome tests and statistical analysis. The research subjects were 30 students enrolled in an Islamic History course at Medan State University. Data collection included questionnaires, interviews, and essay tests. Qualitative techniques were used to analyse interview data, while quantitative methods were applied to questionnaire and essay test data. The results showed a significant improvement in student understanding and engagement. Validation from subject matter experts resulted in an average score of 4.0 (Good), while media experts gave an average score of 3.8 (Fairly Good). Student trials produced an average score of 4.02 (Good). Learning outcomes improved significantly, with the average score rising from 62.33 to 79. The paired sample t-test showed a t-value of -27.55 and a p-value of 0.000, indicating a statistically significant difference. In conclusion, the e-modules effectively improved learning quality, underscoring the need for personalised and adaptive learning approaches.